Positive electrode additive and positive electrode for lithium secondary battery containing the same
The use of lithium cobalt oxide with a surface-adsorbed carbon material addresses the structural instability and low conductivity of conventional additives, enhancing the electrical performance and safety of lithium secondary batteries.
Patent Information
- Application Number
- JP2023515660
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-05-25
- Filing Date
- 2022-05-06
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2042-05-06
AI Technical Summary
Conventional irreversible additives for lithium secondary batteries are structurally unstable, generate gases that cause volume expansion and side reactions, leading to reduced battery performance and safety, and have low electrical conductivity, limiting high-speed charging and discharging capabilities.
A positive electrode additive comprising lithium cobalt oxide with a carbon material adsorbed on its surface, enhancing electrical conductivity and stability by forming a conductive network, thereby reducing gas generation and side reactions.
The additive improves the electrical performance of lithium secondary batteries by increasing charge/discharge capacity, reducing gas generation, and enhancing safety through improved conductivity and structural stability.
Smart Images

Figure 0007616714000001 
Figure 0007616714000002 
Figure 0007616714000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode additive for a lithium secondary battery and a positive electrode for a lithium secondary battery containing the same.
[0002] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0066767 dated May 25, 2021, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference. [Background technology]
[0003] With the development of technology and increasing demand for mobile devices, the demand for secondary batteries as an energy source is rapidly increasing. Among such secondary batteries, lithium secondary batteries, which have high energy density and working potential, long cycle life, and low self-discharge rate, have been commercialized and are widely used.
[0004] Recently, as lithium secondary batteries are used as power sources for medium- to large-sized devices such as electric vehicles, there is an increasing demand for high capacity, high energy density, and low cost of lithium secondary batteries, and the irreversible additives used in electrodes are also required to have higher irreversible capacity. However, there is currently a limit to the development of positive electrode additives having such high irreversible capacity.
[0005] Meanwhile, conventional irreversible additives such as Li6CoO4 are generally manufactured by reacting cobalt oxide with an excess amount of lithium oxide. The irreversible additives manufactured in this way are structurally unstable and generate large amounts of gases such as oxygen gas (O2) and carbon dioxide (CO2) as charging proceeds. Not only do the generated gases induce volume expansion of the electrode assembly, reducing the stability of the battery, but the carbon oxides of carbon dioxide (CO2) induce a side reaction that causes decomposition with the electrolyte, which can act as a major factor in reducing battery performance.
[0006] In addition, the non-reversible additives that are commonly used in the past are nearly non-conductive due to their 2D percolating network, with a resistance of ~10 -11 It exhibits very low powder electrical conductivity of 1.5 S / cm. Such low powder electrical conductivity increases the electrical resistance of the positive electrode, and in this case, it shows a large capacity of over 200mAh / g at a low C-rate, but as the C-rate increases, the performance rapidly decreases as charging and discharging proceeds due to the large resistance, so there is a limit in that high-speed charging and discharging is difficult.
[0007] Therefore, there is a demand for the development of a lithium secondary battery that has a high charge / discharge capacity, a reduced amount of gas generated during charging / discharging, and thus excellent battery safety, as well as a reduced side reaction of the generated gas with the electrolyte and improved electrical conductivity of the positive electrode, thereby providing excellent electrical performance. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Korean Patent Publication No. 10-2019-0078392 Summary of the Invention [Problem to be solved by the invention]
[0009] Therefore, an object of the present invention is to provide a positive electrode for a lithium secondary battery, which has a high charge / discharge capacity and excellent battery safety due to improved gas generation by using an irreversible additive in a positive electrode, and which has excellent electrical performance by reducing side reactions between the generated gas and the electrolyte and improving the electrical conductivity of the positive electrode, and a lithium secondary battery including the same. [Means for solving the problem]
[0010] To solve the above problems, In one embodiment, the present invention comprises: A lithium cobalt oxide represented by the following chemical formula 1, and a carbon material adsorbed on the surface of the lithium cobalt oxide, the carbon material comprising:
[0011] [Chemical formula 1] Li p Co (1-q) M 1 q O4
[0012] In the above chemical formula 1, M 1 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; p and q are 5≦p≦7 and 0≦q≦0.5, respectively.
[0013] Here, the carbon substance may include one or more selected from the group consisting of carbon nanotubes, carbon nanofibers, graphite, graphene, carbon black, ketjen black, and acetylene black.
[0014] The carbon substance may have a surface modified with one or more functional groups selected from the group consisting of a hydroxyl group, a carboxyl group, an amino group, an amide group, a sulfone group, and a sulfide group, and / or may contain on the surface one or more compounds selected from the group consisting of monoethanolamine, diethanolamine, triethanolamine, diethylenetriamine, triethylenetetraamine, trisamino C1-3 alkylamines, poly C1-3 alkyleneamines, and poly C1-3 alkyleneimines.
[0015] The carbon material can also be adsorbed onto more than 70% of the total surface area of the lithium cobalt oxide.
[0016] The carbon substance may be present in an amount of 0.1 to 20 parts by weight based on 100 parts by weight of the lithium cobalt oxide.
[0017] In addition, the average thickness of the adsorbed carbon material may be 10 nm to 200 nm.
[0018] The lithium cobalt oxide may have an average particle size of 0.1 to 10 μm.
[0019] The lithium cobalt oxide may have a tetragonal structure with a space group of P42 / nmc.
[0020] In one embodiment, the present invention provides a method for producing a composition comprising: A positive electrode current collector; There is also provided a positive electrode for a lithium secondary battery, the positive electrode comprising: a positive electrode mixture layer located on the positive electrode current collector and containing a positive electrode active material, the positive electrode additive according to the present invention described above, and a binder.
[0021] In this case, the positive electrode active material may be a lithium metal composite oxide represented by the following Chemical Formula 2:
[0022] [Chemical formula 2] Li x [Ni y Co z Mn w M 2 v ]Ou
[0023] In the above chemical formula 2, M 2 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; x, y, z, w, v, and u are 1.0≦x≦1.30, 0≦y<0.95, 0 <z≦0.5、0<w≦0.5、0≦v≦0.2、1.5≦u≦4.5である。
[0024] The positive electrode active material may be contained in an amount of 80 to 99.5 parts by weight per 100 parts by weight of the positive electrode mixture layer.
[0025] The positive electrode additive may be contained in an amount of 0.1 to 5 parts by weight relative to 100 parts by weight of the positive electrode mixture layer.
[0026] Moreover, the positive electrode may further contain a conductive material. In this case, the content of the conductive material may be 2 parts by weight or less with respect to 100 parts by weight of the positive electrode mixture layer. Effect of the Invention
[0027] The positive electrode additive for lithium secondary batteries according to the present invention contains a carbon material on the surface of the lithium cobalt oxide represented by Chemical Formula 1, thereby improving the low electrical conductivity of the positive electrode additive and improving problems caused by the amount of gas generated during initial charge and discharge (i.e., "activation"). Therefore, the positive electrode and lithium secondary battery containing the same have the advantage of excellent electrical performance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] While the present invention may be modified in many ways and may have a variety of embodiments, a specific embodiment will be described in detail in the detailed description.
[0029] It should be understood, however, that this is not intended to limit the invention to the particular embodiment, but rather to include all modifications, equivalents, or alternatives falling within the spirit and scope of the invention.
[0030] In the present invention, the terms "comprise" or "have" are intended to specify the presence of features, numbers, steps, operations, components, parts, or combinations thereof described in the specification, and should be understood as not precluding the presence or additional possibility of one or more other features, numbers, steps, operations, components, parts, or combinations thereof.
[0031] In addition, in the present invention, when a layer, film, region, plate, or other portion is described as being "on" another portion, this includes not only the case where it is "directly on" the other portion, but also the case where there is another portion in between. Conversely, when a layer, film, region, plate, or other portion is described as being "under" the other portion, this includes not only the case where it is "directly under" the other portion, but also the case where there is another portion in between. In addition, in the present application, being "located on" may include not only the case where it is located at the top, but also the case where it is located at the bottom.
[0032] In addition, in the present invention, a "major component" means 50% by weight or more, 60% by weight or more, 70% by weight or more, 80% by weight or more, 90% by weight or more, 95% by weight or more, or 97.5% by weight or more of the total weight of the composition or specific component, and in some cases, it can also mean 100% by weight when it constitutes the entire composition or specific component.
[0033] In the present invention, "Ah" is a unit of capacity of a lithium secondary battery, and is called "ampere-hour" and means the amount of current per hour. For example, if a battery capacity is "3000mAh", it means that it can be discharged at a current of 3000mA for one hour.
[0034] The present invention will now be described in more detail.
[0035] <Positive electrode additives for lithium secondary batteries> In one embodiment, the present invention comprises: A lithium cobalt oxide represented by the following chemical formula 1, and a carbon material adsorbed on the surface of the lithium cobalt oxide, the carbon material comprising:
[0036] [Chemical formula 1] Li p Co (1-q) M 1 q O4
[0037] In the above chemical formula 1, M 1is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; p and q are 5≦p≦7 and 0≦q≦0.5, respectively.
[0038] The positive electrode additive according to the present invention contains lithium cobalt oxide as a main component, and has a structure in which a carbon material is adsorbed on the surface of the lithium cobalt oxide.
[0039] Here, the lithium cobalt oxide may be one or more compounds represented by the following Formula 1:
[0040] [Chemical formula 1] Li p Co (1-q) M 1 q O4
[0041] In the above chemical formula 1, M 1 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; p and q are 5≦p≦7 and 0≦q≦0.5, respectively.
[0042] The lithium cobalt oxide contains an excess of lithium and can provide lithium to replace lithium consumption that occurs due to irreversible chemical and physical reactions at the negative electrode during initial charging. As a result, the charge capacity of the battery can be increased and the irreversible capacity can be reduced, thereby improving the life characteristics.
[0043] Among them, the positive electrode additive represented by the above formula 1 has a higher lithium ion content than nickel-containing oxides commonly used in the industry, and therefore can replenish lithium ions lost in irreversible reactions during initial activation of the battery, thereby significantly improving the charge / discharge capacity of the battery. Also, compared to iron- and / or manganese-containing oxides commonly used in the industry, there is no side reaction caused by the elution of transition metals during charging and discharging of the battery, and therefore the battery has excellent stability. Examples of lithium cobalt oxides represented by the formula 1 include Li6CoO4, Li6Co 0.5 Zinc 0.5 O4, Li6Co 0.7 Zinc 0.3 It may also include O4.
[0044] The average particle size of the lithium cobalt oxide represented by the above chemical formula 1 may be 0.1 to 10 μm, specifically, 0.1 to 8 μm, 0.1 to 5 μm, 0.1 to 3 μm, 0.5 to 2 μm, 0.1 to 0.9 μm, 0.1 to 0.5 μm, 0.6 to 0.9 μm, 1 to 4 μm, 4 to 6 μm, or 6 to 9 μm. By controlling the average particle size of the lithium cobalt oxide within the above range, the present invention can enhance the irreversible activity of the lithium cobalt oxide and prevent the powder electrical conductivity of the lithium cobalt oxide from decreasing.
[0045] In addition, the lithium cobalt oxide represented by the formula 1 may have a tetragonal crystal structure, and may be included in the space group P42 / nmc having a distorted tetrahedral structure formed by cobalt and oxygen atoms. The positive electrode additive having a distorted tetrahedral structure has a distorted tetrahedral structure formed by cobalt and oxygen atoms, and is structurally unstable, so that a large amount of gas may be generated during initial charge and discharge (i.e., "activation") and / or subsequent charge and discharge, which may induce volume expansion of the electrode assembly, reducing battery performance and safety. However, the positive electrode additive according to the present invention can improve this problem by having a structure containing a carbon material on the surface of the lithium cobalt oxide represented by the formula 1.
[0046] Specifically, the positive electrode additive according to the present invention may have a structure in which a carbon material is physically and / or chemically adsorbed on the surface of the lithium cobalt oxide represented by Chemical Formula 1. Here, "physical adsorption" means that atoms such as lithium (Li), cobalt (Co), oxygen (O) exposed on the surface of the lithium cobalt oxide and functional groups and / or compounds present on the surface of the carbon material interact with each other through weak intermolecular forces such as van der Waals and are fixed. Also, "chemical adsorption" means that atoms such as lithium (Li), cobalt (Co), oxygen (O) exposed on the surface of the lithium cobalt oxide and functional groups and / or compounds present on the surface of the carbon material are fixed through chemical bonds such as hydrogen bonds.
[0047] The carbon substance may include at least one selected from the group consisting of carbon nanotubes, carbon nanofibers, graphite, graphene, carbon black, ketjen black, and acetylene black.
[0048] The carbon material may have a surface modified with a functional group capable of forming a hydrogen bond, or may have a compound containing an amino group on the surface.
[0049] Specifically, the carbon material may be surface-modified with one or more functional groups selected from the group consisting of a hydroxyl group, a carboxyl group, an amino group, an amide group, a sulfone group, and a sulfide group. Such modification may be performed by a method commonly used in the art. For example, the carbon material may be heat-treated under oxygen gas conditions, or, in some cases, may be uniformly mixed / coated with a compound / polymer having the functional group, and then heat-treated or hydrothermal-treated to thermally decompose the compound / polymer, thereby introducing the functional group onto the surface.
[0050] The carbon substance may contain, on the surface thereof, one or more compounds selected from the group consisting of monoethanolamine, diethanolamine, triethanolamine, diethylenetriamine, triethylenetetraamine, trisamino C1-3 alkylamine, poly C1-3 alkyleneamine, and poly C1-3 alkyleneimine. In this case, the carbon substance can be produced by uniformly mixing the carbon substance with the compound and then drying the mixture in a vacuum oven at 50 to 100°C for 10 to 100 hours.
[0051] As described above, the present invention has a structure in which a carbon material having a low powder electrical conductivity is adsorbed on the surface of a lithium cobalt oxide, the surface of which is modified with a functional group such as a hydroxyl group, a carboxyl group, or an amino group, or the surface of which contains a compound such as polyalkyleneamine, and the like, so that a conductive network or conductive path can be formed on the surface of the lithium cobalt oxide, thereby imparting high electrical conductivity. In particular, when a compound such as polyalkyleneamine is contained on the surface of the carbon material, carbon oxides such as carbon monoxide (CO) and carbon dioxide (CO2) formed by electrolyte decomposition during charging and discharging of a lithium secondary battery can be adsorbed, and the carbon oxides react with lithium hydroxide (LiOH) to generate HF or LiF, which promotes gas generation, and thus prevents the activity of the positive electrode active material contained in the positive electrode from decreasing.
[0052] In addition, the carbon material can be adsorbed to 70% or more of the entire surface of the lithium cobalt oxide represented by Chemical Formula 1. Specifically, the carbon material can be adsorbed to 75% or more, 80% or more, 85% or more, 90% or more, 95% or more, 70% to 95%, 75% to 95%, 80% to 95%, or 80% to 90% of the entire surface of the lithium cobalt oxide, and in some cases, the carbon material can be adsorbed to completely coat the entire surface of the lithium cobalt oxide, and have the form of a carbon layer.
[0053] The carbon substance may have a content of 0.1 to 20 parts by weight relative to 100 parts by weight of the lithium cobalt oxide. Specifically, the carbon substance may have a content of 0.1 to 15 parts by weight, 0.1 to 10 parts by weight, 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, 1 to 4 parts by weight, 5 to 10 parts by weight, 6 to 9 parts by weight, 5 to 15 parts by weight, 11 to 19 parts by weight, 16 to 20 parts by weight, or 8 to 14 parts by weight relative to 100 parts by weight of the lithium cobalt oxide.
[0054] Moreover, the average thickness of the carbon substance adsorbed on the surface of the lithium cobalt oxide may be 10 nm to 200 nm, specifically, 10 nm to 150 nm, 10 nm to 100 nm, 10 nm to 90 nm, 10 nm to 70 nm, 20 nm to 60 nm, 50 nm to 150 nm, 50 nm to 90 nm, 90 nm to 120 nm, 130 nm to 190 nm, or 160 nm to 190 nm.
[0055] The present invention controls the surface area ratio, content and / or average thickness range of the carbon material adsorbed on the surface of the lithium cobalt oxide within the above ranges, thereby sufficiently forming a conductive path on the surface of the lithium cobalt oxide, and therefore, compared to a composite in which the lithium cobalt oxide and the carbon material are uniformly mixed, the electrical conductivity of the positive electrode additive can be effectively improved with a small amount of carbon material, and the amount of the conductive material used to improve the electrical conductivity of the positive electrode additive can be reduced. At the same time, the structural stability of the lithium cobalt oxide represented by Chemical Formula 1 can be improved, and side reactions of the lithium cobalt oxide during charging can be suppressed.
[0056] Meanwhile, the positive electrode additive can be prepared by any method that can adsorb and / or coat a carbon material on the surface of lithium cobalt oxide, without any particular limitations.
[0057] As an example, the lithium cobalt oxide represented by Chemical Formula 1 and the carbon material are mixed together with a polymer having a hydroxyl group, a carboxyl group, an amino group, an amide group, a sulfone group and / or a sulfide group in a reactor such as a homomixer, and then pyrolyzed at 500 to 800° C. In this case, the polymer is pyrolyzed by the heat treatment, and the functional group present in the polymer is located between the carbon material and the lithium cobalt oxide, allowing the carbon material to be adsorbed to the lithium cobalt oxide.
[0058] As another example, it can be produced by dispersing a carbon substance in a dispersion medium, adding lithium cobalt oxide, and then irradiating with ultrasonic waves. In this case, the ultrasonic waves can be irradiated at a frequency of 30 kHz to 60 kHz while maintaining a temperature of 20°C to 35°C.
[0059] In the case of a method of manufacturing the lithium cobalt oxide represented by Chemical Formula 1 by heat-treating a mixture of a precursor material and a carbon material precursor, the carbon material may be present not only on the surface of the lithium cobalt oxide but also inside the lithium cobalt oxide. However, the method according to the present invention has the advantage of being able to ensure the structural stability of the lithium cobalt oxide and to effectively improve the electrical conductivity of the positive electrode additive with a small amount of carbon material while realizing high irreversible activity of the lithium cobalt oxide.
[0060] <Positive electrodes for lithium secondary batteries> In one embodiment, the present invention provides a method for producing a composition comprising: A positive electrode current collector; a mixture layer located on the positive electrode current collector and containing a positive electrode active material, the positive electrode additive of the present invention described above, and a binder; The positive electrode additive provides a positive electrode for a lithium secondary battery, which contains a lithium cobalt oxide represented by the following Chemical Formula 1 and a carbon material adsorbed on the surface of the lithium cobalt oxide:
[0061] [Chemical formula 1] Li p Co (1-q) M 1 q O4
[0062] In the above chemical formula 1, M 1 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; p and q are 5≦p≦7 and 0≦q≦0.5, respectively.
[0063] The positive electrode for a lithium secondary battery according to the present invention has a structure in which a mixture layer is formed on a positive electrode current collector, and the positive electrode mixture layer has a configuration containing a positive electrode active material, the above-mentioned positive electrode additive of the present invention, a conductive material, and a binder.
[0064] In this case, the positive electrode active material may be a lithium composite transition metal oxide containing two or more elements selected from the group consisting of nickel (Ni), cobalt (Co), manganese (Mn), aluminum (Al), zinc (Zn), titanium (Ti), magnesium (Mg), chromium (Cr) and zirconium (Zr). For example, the positive electrode active material may be a lithium nickel metal oxide capable of reversible intercalation and deintercalation, as shown in the following Chemical Formula 2:
[0065] [Chemical formula 2] Li x [Ni y Co z Mn w M 2 v ]O u
[0066] In the above chemical formula 2, M 2 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; x, y, z, w, v, and u are 1.0≦x≦1.30, 0≦y<0.95, 0 <z≦0.5、0<w≦0.5、0≦v≦0.2、1.5≦u≦4.5である。
[0067] The lithium nickel composite oxide represented by the above chemical formula 2 is a composite metal oxide containing lithium, nickel, cobalt and manganese, and in some cases, other transition metals (M 2 For example, the positive electrode active material may be doped with LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.9 Co 0.05 Mn 0.05O2, LiNi 0.8 Co 0.1 Mn 0.05 Al 0.05 O2 and LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 O2. As an example, the positive electrode active material is a lithium nickel composite metal oxide represented by Chemical Formula 2, LiNi 0.6 Co 0.2 Mn 0.2 O2 and LiNi 0.8 Co 0.1 Mn 0.1 O2 can be used alone or in combination.
[0068] The content of the positive electrode active material may be 80 to 99.5 parts by weight, specifically 88 to 95 parts by weight, 90 to 95 parts by weight, 86 to 90 parts by weight, or 92 to 95 parts by weight, relative to 100 parts by weight of the positive electrode mixture layer.
[0069] The positive electrode additive may be included in an amount of 0.1 to 5 parts by weight relative to 100 parts by weight of the positive electrode mixture layer, and specifically, the positive electrode additive may be included in an amount of 0.1 to 4 parts by weight, 0.1 to 3 parts by weight, 0.1 to 2 parts by weight, 0.1 to 1 part by weight, 0.5 to 2 parts by weight, 1 to 3 parts by weight, 2 to 4 parts by weight, 1.5 to 3.5 parts by weight, 0.5 to 1.5 parts by weight, or 1 to 2 parts by weight.
[0070] The conductive material may be contained in an amount of 1 to 10 parts by weight, specifically 2 to 8 parts by weight, or 1 to 5 parts by weight, relative to 100 parts by weight of the mixture layer.
[0071] The binder may include one or more resins selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethylmethacrylate, and copolymers thereof. As an example, the binder may include polyvinylidene fluoride.
[0072] The binder may be contained in an amount of 1 to 10 parts by weight, specifically 2 to 8 parts by weight, or 1 to 5 parts by weight, relative to 100 parts by weight of the entire mixture layer.
[0073] In addition, the positive electrode mixture layer may further include a conductive material, in which case the content of the conductive material may be 2 parts by weight or less relative to 100 parts by weight of the positive electrode mixture layer. For example, the conductive material may be included in an amount of 0.1 to 2 parts by weight, 0.1 to 1.5 parts by weight, 0.1 to 1 part by weight, or 0.1 to 0.5 parts by weight relative to 100 parts by weight of the positive electrode mixture layer.
[0074] The conductive material may be one or more carbon materials selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, and carbon fiber. For example, the conductive material may include acetylene black.
[0075] On the other hand, the average thickness of the positive electrode composite layer is not particularly limited, but may be specifically 50 μm to 300 μm, and more specifically, may be 100 μm to 200 μm, 80 μm to 150 μm, 120 μm to 170 μm, 150 μm to 300 μm, 200 μm to 300 μm, or 150 μm to 190 μm.
[0076] In addition, the positive electrode can be a positive electrode current collector having high conductivity without inducing chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, etc. can be used, and in the case of aluminum or stainless steel, those surface-treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode current collector can be formed with fine irregularities on the surface to increase the adhesive force of the positive electrode active material, and can be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc. In addition, the average thickness of the current collector can be appropriately applied to 3 to 500 μm in consideration of the conductivity and total thickness of the positive electrode to be manufactured.
[0077] <Lithium secondary battery> Moreover, in one embodiment, the present invention provides There is provided a lithium secondary battery including the above-described positive electrode according to the present invention, a negative electrode, and a separator interposed between the positive electrode and the negative electrode.
[0078] The lithium secondary battery according to the present invention includes the cathode of the present invention as described above, and can induce delithiation of the cathode additive at a high rate under a low voltage condition below the available voltage during initial charging. Therefore, the amount of oxygen gas generated during subsequent charging and discharging is significantly reduced, and thus the lithium secondary battery has excellent electrical performance and safety.
[0079] The lithium secondary battery of the present invention has a structure including a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode.
[0080] Here, the negative electrode is manufactured by applying a negative electrode active material onto a negative electrode current collector, followed by drying and pressing, and may further include the same conductive material, organic binder polymer, additives, etc. as the positive electrode, as necessary.
[0081] The negative electrode active material may include, for example, a carbon material and a silicon material. The carbon material means a carbon material mainly composed of carbon atoms, and examples of such carbon materials include graphite having a perfect layered crystal structure like natural graphite, soft carbon having a low crystalline layered crystal structure (graphene structure; a structure in which hexagonal honeycomb-shaped carbon planes are arranged in layers), and hard carbon in which such a structure is mixed with a non-crystalline portion, artificial graphite, expanded graphite, carbon fiber, non-graphitizable carbon, carbon black, acetylene black, ketjen black, carbon nanotubes, fullerene, activated carbon, graphene, carbon nanotubes, etc., and preferably, may include one or more selected from the group consisting of natural graphite, artificial graphite, graphene, and carbon nanotubes. More preferably, the carbon material may include natural graphite and / or artificial graphite, and may include at least one of graphene and carbon nanotubes together with the natural graphite and / or artificial graphite. In this case, the carbon substance may contain 50 to 95 parts by weight of graphene and / or carbon nanotubes per 100 parts by weight of the total carbon substance, and more specifically, may contain 60 to 90 parts by weight, or 70 to 80 parts by weight of graphene and / or carbon nanotubes per 100 parts by weight of the total carbon substance.
[0082] The silicon substance is a particle containing silicon (Si) as a metal component as a main component, and is a silicon (Si) particle and a silicon oxide (SiO X , 1≦X≦2) particles. As an example, the silicon material may include silicon (Si) particles, silicon monoxide (SiO) particles, silicon dioxide (SiO2) particles, or a mixture of these particles.
[0083] In addition, the silicon material may have a mixed form of crystalline particles and amorphous particles, and the ratio of the amorphous particles may be 50 to 100 parts by weight, specifically 50 to 90 parts by weight, 60 to 80 parts by weight, or 85 to 100 parts by weight, based on 100 parts by weight of the total silicon material. By controlling the ratio of the amorphous particles contained in the silicon material within the above range, the present invention can improve thermal stability and flexibility without deteriorating the electrical properties of the electrode.
[0084] In addition, the silicon material may include a carbon material and a silicon material, and may be included in an amount of 1 to 20 parts by weight relative to 100 parts by weight of the negative electrode composite layer. Specifically, the silicon material may be included in an amount of 5 to 20 parts by weight, 3 to 10 parts by weight, 8 to 15 parts by weight, 13 to 18 parts by weight, or 2 to 7 parts by weight relative to 100 parts by weight of the negative electrode composite layer.
[0085] By adjusting the contents of the carbon material and silicon material contained in the negative active material within the above ranges, the present invention can reduce the lithium consumption and irreversible capacity loss during the initial charge and discharge of the battery, and improve the charge capacity per unit mass.
[0086] For example, the negative electrode active material may include 95±2 parts by weight of graphite and 5±2 parts by weight of a mixture of silicon monoxide (SiO) particles and silicon dioxide (SiO2) particles uniformly mixed, relative to 100 parts by weight of the negative electrode composite layer. By adjusting the contents of the carbon material and silicon material contained in the negative electrode active material within the above ranges, the present invention can reduce lithium consumption and irreversible capacity loss during initial charging and discharging of the battery, and improve the charging capacity per unit mass.
[0087] In addition, the negative electrode mixture layer may further include a binder to fix the negative electrode active material on the current collector. For example, the negative electrode mixture layer may include any one of polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), polymethacrylic acid (PMAA), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), etc., or a mixture of two or more of them, as a binder.
[0088] In this case, the content of the binder may be 0.5 to 5 parts by weight, specifically 0.5 to 4 parts by weight, or 1 to 3 parts by weight, relative to 100 parts by weight of the negative electrode mixture layer.
[0089] The negative electrode mixture layer may have an average thickness of 100 μm to 200 μm, specifically, 100 μm to 180 μm, 100 μm to 150 μm, 120 μm to 200 μm, 140 μm to 200 μm, or 140 μm to 160 μm.
[0090] In addition, the negative electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and for example, copper, stainless steel, nickel, titanium, calcined carbon, etc. can be used. In the case of copper or stainless steel, it is also possible to use a material that has been surface-treated with carbon, nickel, titanium, silver, etc. In addition, the negative electrode current collector can be formed with fine irregularities on the surface in the same manner as the positive electrode current collector to strengthen the binding force with the negative electrode active material, and can be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc. In addition, the average thickness of the negative electrode current collector can be appropriately applied to 3 to 500 μm in consideration of the conductivity and total thickness of the negative electrode to be manufactured.
[0091] The separator is a thin insulating membrane having high ion permeability and mechanical strength, which is interposed between the positive and negative electrodes. The separator is not particularly limited as long as it is one commonly used in the industry. Specifically, a sheet or nonwoven fabric made of chemically resistant and hydrophobic polypropylene, glass fiber, or polyethylene may be used. In some cases, a composite separator made of a porous polymer substrate such as the sheet or nonwoven fabric and inorganic particles / organic particles coated with an organic binder polymer may be used. When a solid electrolyte such as a polymer is used as the electrolyte, the solid electrolyte may also serve as the separator. The pore diameter of the separator may be an average of 0.01 to 10 μm, and the thickness may be an average of 5 to 300 μm.
[0092] Meanwhile, the positive and negative electrodes may be wound in a jelly roll form and housed in a cylindrical battery, a prismatic battery, or a pouch battery, or may be housed in a pouch battery in a folded or stack-and-folded form, but is not limited thereto.
[0093] The lithium salt-containing electrolyte according to the present invention may be composed of an electrolyte and a lithium salt. The electrolyte may be a non-aqueous organic solvent, an organic solid electrolyte, or an inorganic solid electrolyte.
[0094] Examples of the non-aqueous organic solvent that can be used include aprotic organic solvents such as N-methyl-2-pyrrolidinone, ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, gamma-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.
[0095] Examples of the organic solid electrolyte that can be used include polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, polyagitation lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, and polymeric materials containing ionic dissociation groups.
[0096] Examples of the inorganic solid electrolyte that can be used include nitrides, halides, and sulfates of Li, such as Li3N, LiI, Li5NI2, Li3N-LiI-LiOH, LiSiO4, LiSiO4-LiI-LiOH, Li2SiS3, Li4SiO4, Li4SiO4-LiI-LiOH, and Li3PO4-Li2S-SiS2.
[0097] The lithium salt is a substance that is easily dissolved in a non-aqueous electrolyte, and examples of the lithium salt include LiCl, LiBr, LiI, LiClO4, LiBF4, and LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, (CF3SO2)2NLi, lithium chloroborane, lithium lower aliphatic carboxylates, lithium tetraphenylboronate, imides, etc. can be used.
[0098] In addition, for the purpose of improving charge / discharge characteristics, flame retardancy, etc., the electrolyte may contain, for example, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, aluminum trichloride, etc. In some cases, in order to impart non-flammability, a halogen-containing solvent such as carbon tetrachloride or trifluoroethylene may be further contained, and in order to improve high-temperature storage characteristics, carbon dioxide gas may be further contained, and fluoroethylene carbonate (FEC), propene sultone (PRS), etc. may be further contained.
[0099] The present invention will now be described in more detail with reference to examples and experimental examples.
[0100] However, the following examples and experimental examples are merely illustrative of the present invention, and the content of the present invention is not limited to the following examples and experimental examples.
[0101] <Examples 1 to 4. Production of positive electrode additives> Lithium cobalt oxide, Li6CoO4 or Li6Co, represented by the chemical formula 1 0.7 Zinc 0.3 For 100 parts by weight of O4, the carbonaceous material graphene and polyvinyl alcohol (PVA) were weighed out as shown in Table 1 below, poured into a homo mixer, and mixed at 3,000 rpm for 60 minutes. The mixture was then heat-treated at 750±20°C to produce a cathode additive in which graphene was adsorbed onto lithium cobalt oxide through the hydroxyl groups remaining on the graphene after the polyvinyl alcohol was thermally decomposed. The average particle size of the lithium cobalt oxide was 4±0.5 μm, and the average thickness of the adsorbed carbonaceous material was 100±5 nm.
[0102] [Table 1]
[0103] <Examples 5 and 6. Preparation of positive electrode additive> Lithium cobalt oxide Li6CoO4 or Li6Co shown in chemical formula 1 0.7 Zinc 0.3 For 100 parts by weight of O4, graphene and polyethyleneimine (PEI) were weighed as shown in Table 2, poured into a homo mixer, mixed at 3,000 rpm for 60 minutes, and then vacuum dried at 70±2°C for 10 hours to prepare a cathode additive in which graphene is adsorbed onto lithium cobalt oxide through the amino group of polyethyleneimine. The lithium cobalt oxide had an average particle size of 4±0.5 μm, and the adsorbed carbon material had an average thickness of 180±10 nm.
[0104] [Table 2]
[0105] <Comparative Examples 1 to 4. Production of Positive Electrode Additives> As shown in Table 3 below, Li6CoO4 as lithium cobalt oxide, graphene as carbon material, and polyvinyl alcohol (PVA) were prepared, and the graphene and polyvinyl alcohol were weighed out for 100 parts by weight of lithium cobalt oxide, poured into a homo mixer, and mixed at 3,000 rpm for 60 minutes. The mixture was then heat-treated at 750±20°C to produce a cathode additive in which graphene was adsorbed onto the lithium cobalt oxide through the hydroxyl groups remaining on the graphene after the polyvinyl alcohol was thermally decomposed. The average particle size of the lithium cobalt oxide was 4±0.5μm, and the average thickness of the adsorbed carbon material was 95±2nm.
[0106] [Table 3]
[0107] <Comparative Example 5. Production of Positive Electrode Additive> Lithium oxide (Li2O) and cobalt oxide (CoO) were charged into a reactor with a molar ratio of 3.0 to 3.03 and uniformly dry-mixed for about 30 minutes using a mixer. Next, graphene and polyvinyl alcohol (PVA) as carbon materials were further mixed at 7.5 parts by weight and 4 parts by weight per 100 parts by weight of the lithium oxide and cobalt oxide, respectively, and the prepared raw material mixture was placed in an electric furnace and fired at about 700°C for 10 hours under argon gas (Ar) conditions to obtain lithium cobalt oxide (Li6CoO4) with graphene dispersed inside and on the surface as a positive electrode additive.
[0108] <Experimental Example> In order to evaluate the performance of the positive electrode additive according to the present invention, first, a positive electrode containing the positive electrode additive in the positive electrode mixture layer was produced, and a lithium secondary battery including the positive electrode was fabricated.
[0109] Specifically, N-methylpyrrolidone was first poured into a homo mixer, and 100 parts by weight of the positive electrode slurry solids were mixed with LiNi 0.6 Co 0.2 Mn 0.2 O2 and 97.8 parts by weight of the positive electrode additives prepared in Examples 1 to 6 and Comparative Examples 1 to 5, 0.7 parts by weight of carbon black (average size: 2±0.5 μm) as a conductive material, and 1.5 parts by weight of PVDF as a binder were weighed and added, and mixed at 2,000 rpm for 60 minutes to prepare a positive electrode slurry for a lithium secondary battery. Here, the content of the positive electrode additive per 100 parts by weight of the positive electrode slurry solids (≒ weight of the positive electrode mixture layer) was adjusted to 0.8 parts by weight. The prepared positive electrode slurry was applied to one side of an aluminum current collector, dried at 100 ° C., and rolled to prepare a positive electrode. At this time, the total thickness of the positive electrode mixture layer was 130 μm, and the total thickness of the prepared positive electrode was about 200 μm.
[0110] A negative electrode slurry was prepared by preparing 84 parts by weight of natural graphite and 14 parts by weight of silicon (SiOx, where 1≦x≦2) particles as a negative electrode active material and 2 parts by weight of styrene butadiene rubber (SBR) as a binder for 100 parts by weight of the negative electrode slurry solid content, and carrying out the same method as the method for producing the positive electrode slurry. At this time, the graphite used in the production of the negative electrode mixture layer was natural graphite (average particle size: 0.01 to 0.5 μm), and the silicon (SiOx) particles had an average particle size of 0.9 to 1.1 μm. The prepared negative electrode slurry was applied to one side of a copper current collector, dried at 100 ° C., and rolled to produce a negative electrode. At this time, the total thickness of the negative electrode mixture layer was 150 μm, and the total thickness of the produced negative electrode was about 250 μm.
[0111] The prepared positive and negative electrodes were laminated with a separator (thickness: about 16 μm) made of a porous polyethylene (PE) film interposed between them, and E2DVC was injected as an electrolyte to prepare a full cell type lithium secondary battery.
[0112] Here, "E2DVC" refers to a type of carbonate-based electrolyte, a solution in which lithium hexafluorophosphate (LiPF6, 1.0M) and vinyl carbonate (VC, 2% by weight) are mixed with a mixture of ethylene carbonate (EC): dimethyl carbonate (DMC): diethyl carbonate (DEC) = 1:1:1 (volume ratio).
[0113] The manufactured cell was initially charged and discharged at 22±2°C under the current conditions shown in the table below to measure the initial charge capacity (CC) and initial discharge capacity (DC) of the positive electrode additive, and the ratio (CC / DC) of these was calculated. At this time, the potential range of the battery was 2.5 to 4.25V.
[0114] The following experiments were carried out on each of the manufactured lithium secondary batteries.
[0115] B) Analysis of gas released during charging and discharging For each lithium secondary battery containing the positive electrode additive of the Examples and Comparative Examples, an initial charge (formation) was performed under conditions of 55°C, 3.5V and 1.0C, and 50 charge / discharge cycles were performed under conditions of 45°C and 0.3C / 0.3C to measure the total amount of gas and the amount of carbon oxides (CO and CO2) generated during charge / discharge. The results are shown in Table 4 below.
[0116] b) Evaluation of electrode resistance In order to evaluate the electrical conductivity of the positive electrode containing the positive electrode additive according to the present invention, each lithium secondary battery was adjusted to SOC 50% and then subjected to high-speed discharge for 10 seconds to measure the resistance of the secondary battery. The results are shown in Table 4 below.
[0117] C) Evaluation of charge / discharge capacity and capacity retention rate Each lithium secondary battery was charged at a temperature of 25°C with a charging current of 0.1C to a charge end voltage of 4.2 to 4.25V, and activated by charging until the current density at the end voltage became 0.01C. Thereafter, the battery was discharged at a discharge current of 0.1C to a charge end voltage of 2V, and the initial charge / discharge capacity per unit mass was measured. Next, the battery was repeatedly charged / discharged 50 times at 45°C and 0.3C, respectively, to measure the capacity during charge / discharge, and the charge / discharge capacity retention rate after 50 charge / discharge cycles was calculated. The results are shown in Table 4 below.
[0118] d) Evaluation of fast charging characteristics The fast charging efficiency of each lithium secondary battery was calculated by charging and discharging at a current of 0.1 C, and then charging at a current of 5.0 C. Here, the fast charging efficiency was calculated as the ratio of the capacity charged at a current of 0.1 C to the capacity charged at a current of 5.0 C (5.0 C / 0.1 C), and the results are shown in Table 4 below.
[0119] [Table 4]
[0120] As shown in Table 4, the lithium secondary battery using the positive electrode additive of the embodiment containing a carbon material on the surface of the lithium cobalt oxide represented by Chemical Formula 1 according to the present invention generates a small amount of gas during charging and discharging, and in particular, the lithium secondary battery containing the positive electrode additive manufactured in Examples 5 and 6 generates a reduced amount of carbon oxide such as CO and CO2. In addition, it was confirmed that the lithium secondary battery containing the positive electrode additive of the embodiment had an electrode resistance of 0.58Ω or less. In addition, the lithium secondary battery containing the positive electrode additive of the embodiment showed a high initial charge and discharge capacity of 103.8mAh or more, and maintained this at 90.7% or more even after 50 repeated charge and discharge cycles, and the lithium secondary battery showed a high efficiency of 90.2% during high-speed charging.
[0121] From these results, it can be seen that the positive electrode additive according to the present invention can improve the low electrical conductivity of the positive electrode additive by incorporating a carbon material on the surface of the lithium cobalt oxide represented by Chemical Formula 1, and is also effective in improving problems caused by the amount of gas generated during initial charge and discharge (i.e., "activation"). Therefore, it can be seen that the positive electrode and lithium secondary battery containing the same have excellent electrical performance.
[0122] Although the present invention has been described above with reference to preferred embodiments thereof, it will be understood that a person skilled in the art or having ordinary knowledge in the art can make various modifications and variations to the present invention without departing from the spirit and technical scope of the present invention as described in the claims below.
[0123] Therefore, the technical scope of the present invention should not be limited to the contents described in the detailed description of the specification, but should be defined by the claims.
Claims
1. A lithium cobalt oxide represented by the following chemical formula 1, a carbon material adsorbed on the surface of the lithium cobalt oxide; The carbonaceous material is adsorbed to more than 70% of the total surface area of the lithium cobalt oxide. A cathode additive having an average thickness of adsorbed carbon material of 50 nm to 200 nm: [Chemical formula 1] Li p Co (1-q) M 1 q O 4 In the above Chemical Formula 1, M 1 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; p and q are 5≦p≦7 and 0≦q≦0.5, respectively.
2. 2. The positive electrode additive according to claim 1, wherein the carbon material comprises at least one selected from the group consisting of carbon nanotubes, carbon nanofibers, graphite, graphene, carbon black, ketjen black, and acetylene black.
3. 2. The positive electrode additive of claim 1, wherein the carbon material is surface-modified with one or more functional groups selected from the group consisting of hydroxyl groups, carboxyl groups, amino groups, amide groups, sulfone groups, and sulfide groups.
4. The positive electrode additive according to claim 1, wherein the carbonaceous substance contains on its surface one or more compounds selected from the group consisting of monoethanolamine, diethanolamine, triethanolamine, diethylenetriamine, triethylenetetraamine, trisamino C1-3 alkylamine, poly C1-3 alkyleneamine and poly C1-3 alkyleneimine.
5. 2. The cathode additive of claim 1, wherein the carbonaceous material has a content of 0.1 to 20 parts by weight per 100 parts by weight of the lithium cobalt oxide.
6. The cathode additive of claim 1, wherein the lithium cobalt oxide has an average particle size of 0.1 to 10 μm.
7. Lithium cobalt oxide has a space group of P4 2 The positive electrode additive of claim 1 having a tetragonal crystal structure in which N is 0.1 to 0.
1.
8. A positive electrode current collector; A positive electrode for a lithium secondary battery comprising: a positive electrode mixture layer located on the positive electrode current collector, the positive electrode mixture layer containing a positive electrode active material, the positive electrode additive according to claim 1, and a binder.
9. The positive electrode for a lithium secondary battery according to claim 8, wherein the positive electrode active material is a lithium metal composite oxide represented by the following chemical formula 2: [Chemical formula 2] Li x [Ni y Co z Mn w M 2 v ]O u In the above Chemical Formula 2, M 2 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; x, y, z, w, v, and u are within the ranges of 1.0≦x≦1.30, 0≦y<0.95, 0<z≦0.5, 0<w≦0.5, 0≦v≦0.2, and 1.5≦u≦4.5, respectively.
10. 9. The positive electrode for a lithium secondary battery according to claim 8, wherein the positive electrode active material is contained in an amount of 80 to 99.5 parts by weight per 100 parts by weight of the positive electrode mixture layer.
11. 9. The positive electrode for a lithium secondary battery according to claim 8, wherein the positive electrode additive is contained in an amount of 0.1 to 5 parts by weight per 100 parts by weight of the positive electrode mixture layer.
12. The positive electrode further comprises a conductive material, 9. The positive electrode for a lithium secondary battery according to claim 8, wherein the conductive material is contained in an amount of 2 parts by weight or less per 100 parts by weight of the positive electrode mixture layer.
Citation Information
Patent Citations
Graphite-oxide-coated lithium ion battery positive electrode material
CN111106317A
Carbon-coated lithium-rich oxide composite material and preparation method thereof
CN111725576A
Nonaqueous electrolyte battery
JP1997147863A
Lithium ion secondary battery
JP2019061751A
Additives for positive electrode, method for manufacturing the same, positive electrode including the same, and lithium recharegable battery including the same
KR1020190078392A